Legal Risks of Article 47 of Law No. 3/2025 on the Assignment of Active-Duty TNI Personnel to Civilian Office - Febriyan Victorinus Lolobua; Lisma Lumetut (Journal of Law, Society and Living Norms, 2025)
The amendment of Law No. 34/2004 through Law No. 3/2025 raises significant legal risks regarding the separation between military and civilian authority in Indonesia. The revised Article 47 expands the scope for assigning active-duty military personnel to fourteen ministries and agencies and permits broader transfers upon resignation or retirement. This study examines the legal risks and institutional implications of these provisions using a normative legal research method grounded in statutory analysis and official documents. The findings indicate a growing discrepancy between formal legal requirements and practical implementation, illustrated by the appointment of an active-duty officer as President Director of a state-owned enterprise outside the statutory list. This revolving-door pattern weakens legal certainty, expands potential conflicts of interest, and blurs civil–military boundaries established after the 1998 Reform. The study concludes that without strict enforcement of legal safeguards, the amendment risks undermining civilian supremacy, diluting accountability mechanisms, and enabling the resurgence of dual-function practices. Strengthening institutional oversight is essential to maintain democratic governance and uphold the principle of civilian control.